Antibiotic resistance in E. coli Antibiotic resistance in E. coli - may.aljilawi (Karbala Journal of Medicine, 2024)
the treatment of bacterial illnesses is a complicated task because this micro-organism have the ability to develop a wide spectrum of antibiotic resistance and in different mechanisms. Antimicrobial drugs are typically categorized according to their primary mode of action . for example β-lactams and glycol-peptide agents may interfere with cell wall synthesis, while macrolides and tetracycline disturb bacterial protein synthesis , another group (fluoroquinolones and rifampin) can inhibit nucleic acid and genetic material synthesis, while inhibition of a metabolic pathway is a mechanism of trimethoprim_sulfamethoxazole agents , interference of the structures of bacteria membranes structure and function is a characteristics of -polymyxins anddaptomycin . Antibiotic resistance can develop in bacteria in a variety of ways. They may be naturally resistant to antimicrobial treatments, or they may be resistant due to genetic alterations or the transmission of a resistance allele from another species. The development of effluxing systems that protect the medicine from accomplishing its aim intracellularly, adapting the medication's area of action, or providing a substitute biosynthetic activity that avoids the drug's effects could all be possible with a new resistant allele. By conjugation, transformation, or transduction, antimicrobial-inclined microorganisms can gain current genetic material from resistant bacteria, with transposons commonly assisting the inclusion of multiple resistance genes into the host's genome or plasmids. Antibacterial therapies provide selection stress, which allows new bacteria to emerge.